Determinants of Profitability of Property and Real Estate Companies Listed on Stock Exchange: The Case of Indonesia - Pratiwi, Yeni; Kurniasih, Augustina (Universitas Mercu Buana, 2021)
This study aimed to examine and analyze the effect of liquidity, activity, leverage, and company growth on profitability. The objects of this research were property and real estate companies listed on the Indonesia Stock Exchange in 2013-2017. The research sample was selected using the purposive sampling method. The research population comprised of 48 companies, in which 31 companies met the sample criteria. The analytical method used in this study was panel data regression. The results showed that the best panel model was the fixed effect model. It was found that liquidity, activity, leverage, and company growth simultaneously significantly influenced profitability. Partially, the company’s activities and growth had a positive and significant effect on profitability, leverage had a negative and significant effect on profitability, while liquidity had no significant effect on profitability. Activity was the variable which had the biggest effect on profitability.